Osnovy i perspektivy bozrastnogo somatotipirovaniya - Dorochov, R. N. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The author of the article briefly represented more than 40 years long of his faculty's scientific researches in the field of growing organism's constitutional diagnostics. Special scheme of children's constitutional analysis, based on longitudes' materials, statistic and computer processing of digital materials had been elaborated. The given scheme permits to predict the main motor characteristics of children's organism and to recommend typical training programs for children of different somatic types.